DIGITAL MARKETING STRATEGY ON BUSINESS PERFORMANCE WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN GORONTALO - Darman; Patamani, Flora; Landjani, Nur Afni (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The growth of MSMEs in Gorontalo Province plays a significant role in driving the regional economy, yet challenges in utilizing digital marketing strategies remain a major obstacle to optimizing business performance. On the other hand, customer satisfaction is a key factor that can strengthen the relationship between marketing strategies and business outcomes. This study aims to analyze the effect of digital marketing strategies on MSME business performance in Gorontalo with customer satisfaction as a mediating variable. A quantitative approach was employed, involving 52 purposively selected MSME respondents. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that digital marketing strategies have a direct and significant effect on business performance with a T-statistic value of 2.003 and a P-value of 0.045. Customer satisfaction also has a direct and significant effect on business performance with a T-statistic of 5.699 and a P-value of 0.000. Furthermore, the mediation analysis reveals that customer satisfaction significantly mediates the relationship between digital marketing strategy and business performance (T-statistic = 5.232; P-value = 0.000). These findings highlight the critical role of customer satisfaction in enhancing the effectiveness of digital marketing. Therefore, MSME actors are encouraged to focus not only on technical aspects of digital marketing but also on service quality and customer satisfaction in a comprehensive manner.